2016
DOI: 10.21512/bbr.v7i3.1792
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ownership Structure, Profitability, Leverage, and Firm Size on Corporate Social Responsibility (CSR)

Abstract: Corporate Social Responsibility (CSR), indicator used was the index of CSR disclosure with 64 companies listed in Indonesia Stock Exchange period of 2012 as the samples. This research used multiple regression analysis. The results show that institutional ownership, managerial and foreign has no effect on CSR. This indicates that the ownership structure could not improve CSR in the company. On the contrary, profitability has an influence on CSR. It indicates that companies with high profits have the fund flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
7
12
1
2
Order By: Relevance
“…Inventory intensity (INV) is positively associated with all five CSR variables. LEV is negatively associated with all CSR scores except governance scores (GOV), suggesting that high-leveraged firms engage in less CSR, consistent with Swandari and Sadikin (2016). This is because a high debt ratio requires large interest payments and hence leaves less budget to fund CSR programs.…”
Section: Results Of Multivariate Regressionssupporting
confidence: 53%
“…Inventory intensity (INV) is positively associated with all five CSR variables. LEV is negatively associated with all CSR scores except governance scores (GOV), suggesting that high-leveraged firms engage in less CSR, consistent with Swandari and Sadikin (2016). This is because a high debt ratio requires large interest payments and hence leaves less budget to fund CSR programs.…”
Section: Results Of Multivariate Regressionssupporting
confidence: 53%
“…Additionally, Haniffa and Cooke (2005) suggest considering the values, motives and choices of those involved in CSR-related decisions within the company. Extant literature also supports this line of argument (Amran and Devi, 2008, Said et al, 2009, Meutia et al, 2017, Swandari and Sadikin, 2016, and Cahyani and Suryaningsih, 2016 who found foreign ownership has no significant influence on CSR.…”
Section: Foreign Ownership and Firm Social Performancementioning
confidence: 73%
“…Other studies highlighted the relation between CSR and financial leverage like the study of (Fbio, 2013) who concluded that CSR had an appositive effect on the cost of debt. (Fifi, 2016) found a negative relation between applying the activities of CSR and the leverage of the firm on the other side there are other studies supported the idea that there is a relation between the firms value and the CSR like (Yingix, 2013) who concluded that applying CSR activities affect the performance of the firm. (Kandhar, 2107) found that practicing CSR activities will lead to higher firm value.…”
Section: Conclusion and Recommendationmentioning
confidence: 87%